‘Mixed marriage', citizenship and the policing of intimacy in contemporary France - Kringelbach, H (International Migration Institute, 2013)
This paper examines the ways in which recent family migration policy and its practice in the form of enquiries into the character of bi-national marriages ('mixed marriages’, in French terminology) shape the experience of citizenship in contemporary France. Like other European states, France has recently come to regard bi-national marriage as a 'weak link’ in immigration control, and as a result there is growing focus on policing marriage between French and non-EU citizens, particularly from countries with high numbers of migrants to France. Successive laws passed between 2003 and 2006 have thus made it increasingly difficult for foreign spouses to obtain residence rights, and eventually citizenship. Nevertheless, marriage remains a privileged route to citizenship for many migrants, partly as a result of the difficulty to secure longer-term legal status via other routes. Bi-national marriage thus accounts for an increasing percentage of new French citizens. Since 2006 however, French-foreign couples wishing to marry, or to apply for a spouse visa after being married abroad, have been required to demonstrate the genuine character of their romantic attachment to state agents with a powerful mandate to determine the outcome of applications. How, then, do individuals experience this growing intrusion of the state into their intimacy? How do bureaucratic practices affect the subjective experience of citizenship? This paper addresses these questions by drawing on fieldwork with couples and their families as well as a civic association, and a limited number of state agents. The paper suggests that the policing of intimacy in contemporary France intensifies existing distinctions between 'good’ and 'failed’ citizens. Ultimately, this paper seeks to make an original contribution to the growing literature on changing notions of citizenship in modern states.